The Quality of Education Based on Local Wisdom: The Principal of Madrasah Review - Hasan, Mardhiah; Arwandi, Tesar; Nursita, Lisa; Kamal, St Ibrah Mustafa (JURNAL AL-TANZIM, 2022)
This study was conducted to know the leadership of the madrasah principal in improving the quality of education based on local wisdom in MAN Kepulauan Selayar. This type of research is descriptive qualitative with a case study approach. The method of data collection was conducted by interviewing the principal, teachers, and education staff at MAN Selayar Islands and conducting observations and documentation. The data analysis technique was carried out through four stages: data reduction, data presentation, comparative analysis, and concluding. The results showed that there were efforts made by the head of Madrasah to improve the quality of education at MAN Kepulauan Selayar, namely: 1) Fostering extracurricular activities as a forum for channeling talents and interests of students; 2) the formation of a work team; 3) perform supervision; 4) establish and maintain communication with various parties. This research has implications for the importance of the role of leaders in managing change to create superior quality.